Leonardo a dream of flight - Carver, Brent; Felton, David; Smith, Cedric; King, Allan, 1930-2009.; Storey, Raymond; Devine, David; Mozer, Richard; Devine Entertainment Corporation; Home Box Office (Firm) (Toronto, Ont. : Devine Entertainment, 2002)
A young boy encourages Leonardo da Vinci to pursue his passion and study winged creatures. Their dreams lead to the conquest of the skies.
DVD release of 1997 production.
The Inventor's Specials as seen on HBO.
Special features: "The life and times of Leonardo da Vinci"; full music soundtrack; production notes; cast and crew credits.
Created and produced by David Devine and Richard Mozer ; written by Raymond Storey ; directed by Allan King.
Brent Carver, David Felton, Cedric Smith, Tom Melissis, Natascia A. Diaz, Brenda Bazinet, Leon Pownall.
DVD; Dolby Digital stereo.
Keywords: Leonardo, -- da Vinci, -- 1452-1519 -- Juvenile films; Artists -- Italy -- Biography -- Juvenile films; Inventors -- Italy -- Biography -- Juvenile films; Biographical films; Television programs for children; Video recordings for hard of hearing people